EFFECT OF MULTI PASS HIGH ENERGY MILLING ON MORPHOLOGY AND RHEOLOGICAL PROPERTIES OF CARBON NANOTUBES - Darsono, Nono (Jurnal Metalurgi, 2014)
EFFECT OF MULTI PASS HIGH ENERGY MILLING ON MORPHOLOGY AND RHEOLOGICAL PROPERTIES OF CARBON NANOTUBES. Multi pass high energy milling was utilized in order to cut and disperse carbon nanotubes (CNTs) suspension. The purpose is to maintain the crystallinity and suppress the damage. One until five passes gave increase in D- to G-band ratio which means increasing the damage, at the value range from 0.1 to 0.2. The ratio is still lower compare 2-hour high energy milling and 120-hour conventional ball milling, at the value of 0.5 – 0.3. The rheological properties was not altered dramatically. It is indicated that the milling only tears down the aggeregates into small fraction of entangled CNTs treads.